In vitro Effect of Arnebia densiflora and Artemisia annua Plant Extracts against Theileria annulata Schizonts - Girisgin, O.; Kürkcüoglu, M.; Girisgin, A. O. (Agricultural Research Communication Centre, 2023)
Background: This study investigated the in vitro activities of naphthoquinones and artemisinin contained in the extracts obtained from Arnebia densiflora and Artemisia annua plants against peripheral blood mononuclear cells infected with Theileria annulata schizonts. For this purpose, the n-hexane extract of A. densiflora and the petroleum ether and methanol extracts of A. annua were obtained. Methods: Non-infected and infected cells were cultivated and 2 ?106 cells were seeded in each well in 0.5 ml of RPMI 1640 medium. The n-hexane extract of A. densiflora was tested six times at concentrations of 125, 62.5, 15.625, 7.8125 and 3.9062 mg/ml. A. annua petroleum ether and methanol extracts were also tested six times at 125, 62.5, 31.25, 15.625, 7.8125, 3.9062 and 1.9531 mg/ ml concentrations on PBMCs. A Mann-Whitney U test was used to determine differences between control and experimental groups. Result: The A. densiflora extract killed both non-infected and infected cells at significant levels (P<0.05) compared to the control group at all tested concentrations. A. annua methanol extract had no adverse effect on non-infected cells and the effect on infected cells was insufficient, with the only observed significant effect at a concentration of 125 & mu;g/ml. The A. annua petroleum ether extract had no adverse effect on non-infected cells and killed infected cells at significant levels (P<0.05) at concentrations of 15.625 & mu;g/ml and above at 24 hours. At 48 hours, all infected cells were killed at a concentration of 62.5 & mu;g/ml. In conclusion, A. annua petroleum ether extract can be used in future in vivo studies for Theileriosis at these effective concentrations.
Keywords: Arnebia densiflora; Artemisia annua; Artemisinin; Naphthoquinones; Theileria annulata